Consider H. Willett, Village Attorney, Laws and Ordinances Governing the Village of Hyde Park Together with Its Charter and General Laws Affecting Municipal Corporations; Special Ordinances and Charters under Which Corporations Have Vested Rights in the Village. Also, Summary of Decisions of the Supreme Court Relating to Municipal Corporations, Taxation and Assessments, Page 61, § 8 - (:unkn) unknown (General Publisher, 1876)
Prohibited firing or discharging any cannon, gun, fowling piece, pistol, or firearms of any description, or fire, explode, or set off any squib, crackers, or other thing containing powder, or other combustible, or explosive material on Sundays.
--
Keywords: DISCHARGE